การบริหารงานตามหลักธรรมาภิบาลขององค์กรปกครองส่วนท้องถิ่น อำเภอนาด้วง จังหวัดเลย - สงกาผัน, ศตวรรษ (วารสารศรีล้านช้างปริทรรศน์, 2021)
การวิจัยเรื่องการบริหารงานตามหลักธรรมาภิบาลขององค์กรปกครองส่วนท้องถิ่นอำเภอนาด้วง จังหวัดเลยนี้ เป็นการวิจัยเชิงสำรวจ มีวัตถุประสงค์เพื่อ (1) ศึกษาความคิดเห็นเกี่ยวการบริหารงานตามหลักธรรมาภิบาลของขององค์กรปกครองส่วนท้องถิ่น อำเภอนาด้วง จังหวัดเลย และ (2) เปรียบเทียบขององค์กรปกครองส่วนท้องถิ่น อำเภอนาด้วง จังหวัดเลย จำแนกตาม อายุ และระดับการศึกษา ประชากร ที่ใช้ในการศึกษาครั้งนี้คือ พนักงานส่วนตำบลและลูกจ้างในองค์กรปกครองส่วนท้องถิ่น อำเภอนาด้วง จังหวัดเลย จำนวน 212 คน กลุ่มตัวอย่างจำนวน 139 คนโดยวิธีการใช้สูตรการคำนวณขนาดตัวอย่างด้วยวิธีของ Taro Yamane เครื่องมือที่ใช้ในการศึกษาเป็นแบบสอบถาม ประกอบไปด้วยเนื้อหา 2 ส่วน และสถิติที่ใช้ในการวิเคราะห์ข้อมูล คือสถิติพรรณนา ได้แก่ จำนวน ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐานสำหรับศึกษาข้อมูลทั่วไปของกลุ่มตัวอย่าง สถิติเชิงอนุมาน ได้แก่ T-test และ F-test             ผลการวิจัยพบว่า ความคิดเห็นเกี่ยวกับการบริหารงานตามหลักธรรมาภิบาลขององค์กรปกครองส่วนท้องถิ่นอำเภอนาด้วง จังหวัดเลยโดยภาพรวมอยู่ในระดับมาก (x̅  = 3.56, S.D. = 0.87) และเมื่อพิจารณารายด้าน พบว่า ด้านที่มีค่าเฉลี่ยสูงสุด คือ ด้านหลักความรับผิดชอบ (x̅  = 3.67, S.D. = 0.97) รองลงมา คือ ด้านหลักความโปร่งใส (x̅ = 3.57, S.D.= 1.09) และด้านที่มีค่าเฉลี่ยน้อยที่สุด คือ ด้านหลักการมีส่วนร่วม (x̅  = 3.44, S.D. = 0.92) ผลการเปรียบเทียบความคิดเห็นเกี่ยวกับการบริหารงานตามหลักธรรมาภิบาลขององค์กรปกครองส่วนท้องถิ่นอำเภอนาด้วง จังหวัดเลย โดยจำแนกตามอายุ และระดับการศึกษา โดยภาพรวม พบว่า ไม่มีความแตกต่างกัน                  The research, titled “Good Governance-based Administration of Local Administrative Organizations, Na Duang District, Loei Province,” was conducted by the survey research methodology. The objectives of the research were (1) to study the opinions of people on administration, based on good governance, of local administrative organizations in Na Duang district, Loei province, and (2) to compare the people’s opinions on good governance-based administration, Na Duang district, Loei province, classified by their age and educational level. The samples of the research were 139 people from five local administrative organizations, Na Duang district, Loei province, selected by Taro Yamane’s sampling method (Yamane, 1973). The instruments used for data collection comprised of the five-point rating scale questionnaire, and the descriptive statistics used for data analysis consisted of percentage, mean, and standard deviation whereas the statistics used for the research hypothesis were the t-test and one way analysis of variance (ANOVA).                The findings of the research were as follows: The opinions of people on administration based on good governance of local administrative organizations, Na Duang district, Loei province, was found to be overall at a high level (x̅  = 3.56, S.D. = 0.87). Separately considered in the descending order, responsibility was found to be at the highest level (x̅ = 3.67, S.D. = 0.97), followed by transparency (x̅ = 3.57, S.D. = 1.09), and cooperation was found to be at the lowest level (x̅ = 3.44, S.D. = 0.92). The comparison of people’s opinions on good governance-based administration of local administrative organizations, Na Duang district, Loei province, classified by their gender and educational level, was found not to be different.